Effect of Green Fluorescent Protein (GFP) on the Development of Canine Intergeneric Embryo= Pengaruh Green Fluorescent Protein (GFP) Pada Perkembangan Anjing Dari Embryo Intergeneris. - Yuda Heru Fibrianto (Jurnal Sain Veteriner, 2006)
The present study investigated the effect of green fluorescent protein on the development of canine intergeneric clone embryo with bovine oocyte recipient. Cumulus oocyte complexes (COCs) were collected from slaughterhouse and matured in TCM-199 supplemented with 10% (v/v) fetal bovine serum (FBS) (Life Technologies), 0.005 U/m1 bovine FSH (AntrinÂ®, Denka Kanagawa, Japan) and 1 pg/m1 estradiol (Sigma-Aldrich) at 39 Â°C in a humidified atmosphere of 5% CO2 in air and donor cell tranfected with enhanced green fluorescent protein. In this experiment GFP have no negative effect in fusion or embryo development but the expression rate were decreased in 2 cell stage and then the expression gradually decreased with progression of embryo development.